2014
DOI: 10.1007/s11606-013-2748-y
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Students from a Brazilian Medical School Regarding Online Professionalism

Abstract: INTRODUCTION:Unprofessional online behavior by medical students or physicians may damage individual careers, and the reputation of institutions and the medical profession. What is considered unprofessional online behavior, however, is not clearly defined and may vary in different cultures. OBJECTIVES: To determine the frequency with which students from a Brazilian Medical School come across ten given examples of unprofessional online behavior by medical students or physicians, and gather the opinions of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 13 publications
2
29
0
5
Order By: Relevance
“…Estudos 14 .Já no presente estudo, em relação à opinião dos estudantes sobre o impacto de postagens na reputação do médico, 79,2% (106) deles concordam parcialmente ou totalmente em que "Certos conteúdos do perfil pessoal do Facebook do médico podem difamar a reputação do mesmo". Entende-se por "reputação" o conceito atribuído a alguém.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudos 14 .Já no presente estudo, em relação à opinião dos estudantes sobre o impacto de postagens na reputação do médico, 79,2% (106) deles concordam parcialmente ou totalmente em que "Certos conteúdos do perfil pessoal do Facebook do médico podem difamar a reputação do mesmo". Entende-se por "reputação" o conceito atribuído a alguém.…”
Section: Discussionunclassified
“…Foram reportados comportamentos que divergem do recomendado por códigos de ética, guidelines e orientações de comportamento em redes sociais entre estudantes de Medicina de alguns países, inclusive de estudantes brasileiros 4,14 . Com base nesses dados, em busca de alternativas diante desses impasses, surge o questionamento: algum aspecto da educação médica na graduação tem associação com esses comportamentos?…”
Section: Introductionunclassified
“…This intimacy and facility of use regarding SNSs tools may have an impact on professionalism on the Internet. [26][27][28][29] In order for health care faculty and students to avoid inappropriate online behavior, some US universities have created polices to guide behavior both on-and offline.…”
Section: Professionalism In Social Mediamentioning
confidence: 99%
“…4 Less than 15 % of the Brazilian students in this study report receiving any structured learning in this area. 1 While the potential consequences of online behaviour may seem intuitive, the fact that these students condemned violation of patient privacy, yet did not find the case vignette depicting the posting of pictures of pediatric patients inappropriate is telling of incongruent judgment in this area. That students judged certain online behaviours more unacceptable from faculty also indicates a potential lack of awareness of the 'permanent' and public nature of the online world and how inappropriate posts may impact a student's career long after they have left the classroom.…”
mentioning
confidence: 97%
“…While users of online forums and networking sites may make the distinction between personal and professional posts, posts intended as 'personal' can have negative professional ramifications. Rocha et al 1 surveyed 350 Brazilian Medical Students on the frequency with which they had observed ten categorized unprofessional online behaviours. These ranged from 14 % (patient privacy) to 85 % (photos of alcohol consumption).…”
mentioning
confidence: 99%